Acylated Ghrelin Level Response to Daily Step in the Post-Menopause Active and Sedentary Elderly Women - Farzad Nazem; Zohreh Hosainzadeh; Mohammad Faramarzi (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: Plasmatic total ghrelin levels (ie, acylate & unacylated isoformes) are changeable during malnutrition, starvation regime, exercise bouts, obesity and hyperglycemia conditions. Studies have reported increases, decreases or no change in total ghrelin concentrations as a resultsresults of exercise. WalkingSince walking is used as a movement current pattern with a different lifestyle conditions, especially in several social jobs activities of daily livings of the middle-aged and elderly, the aim of the present study is to evaluate whether therelationship betweenthe number of step per day steps per day andwith acylated ghrelin of menopausal women is related to different life styles.as well, the effects of physical activity volume on this peptide hormone. Methods & Materials: Daily step volumes voluntarily were measured in the health postmenopausal women (n=40) by the electronic pedometer. Subjects (aged 55.9±4.6) divided by as active group (AG=20) and sedentary group (SG=20). Results: Daily step average in the AG (8022±2659 step/day) significantly was higher than SG (3450±913 step/day) (P<0.001). Acylated ghrelin and Insulin concentrations were markedly not different in AG (195.4±131 pg/ml, 9.2±3.03 μU/ml respectively) and SG (165.4±73 pg/ml, 11.5±4.7 μU/ml respectively) as well, step per day were not associated with these hormones. There was a significant difference in body composition variables (BMI, %BF, WHR) among 2 groups and significant inverse correlations were found between activity and body composition variables in women. Conclusion: According to the results, it is recommended that trainers, organizations and institutions that deal with the elderly, use the cycling and walking exercises, especially walking and jogging to reduce the risk of further problem in these people.